Macroeconomic Forces and Stock Prices: Evidence from the Bangladesh Stock Market - Mashrur Mustaque Khan; Ahmed Sadek Yousuf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The study examines the influence of a selective set of macroeconomic forces on stock market prices in Bangladesh. The Dhaka Stock Exchange All-Share Price Index (DSI) is used to represent the prices in the stock market while deposit interest rates, exchange rates, consumer price index (CPI), crude oil prices and broad money supply (M2) are selected to represent the macroeconomic variables affecting the stock prices. Using monthly data from 1992m1-2011m6, several time-series techniques were used which include Cointegration, Vector Error Correction Model (VECM), Impulse Response Functions (IRF) and Variance Decompositions (VDC). Cointegration analysis, along with the VECM, suggests that interest rates, crude oil prices and money supply are positively related to stock prices, exchange rates are negatively related to stock prices, and CPI is insignificant in influencing the stock prices, in the long-run. Both the IRF and VDC suggest that shocks to macroeconomic variables explain a small proportion of the forecast variance error of the DSI, but these effects persist for a long period.
Keywords: C22; E44; E58; G12; 330; Asset Prices; Macroeconomic Factors; Dhaka Stock Exchange; Cointegration; VEC